2016
DOI: 10.1074/jbc.m116.746164
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling (SOCS)1 Regulates Interleukin-4 (IL-4)-activated Insulin Receptor Substrate (IRS)-2 Tyrosine Phosphorylation in Monocytes and Macrophages via the Proteasome

Abstract: Allergic asthma is a chronic lung disease initiated and driven by Th2 cytokines IL-4/-13. In macrophages, IL-4/-13 bind IL-4 receptors, which signal through insulin receptor substrate (IRS)-2, inducing M2 macrophage differentiation. M2 macrophages correlate with disease severity and poor lung function, although the mechanisms that regulate M2 polarization are not understood. Following IL-4 exposure, suppressor of cytokine signaling (SOCS)1 is highly induced in human monocytes. We found that siRNA knockdown of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 99 publications
2
52
0
1
Order By: Relevance
“…In addition to STAT6 activation, the IL‐4R complexes activate other signalling pathways that contribute to the regulation of allergic responses. One pathway involves the binding of the insulin receptor substrate 1/2 (IRS1/2) proteins at Y500 of the human IL‐4Rα, which then act to link the IL‐4R with several downstream signalling pathways, most notably the phosphoinositide 3‐kinases (PI3K)‐AKR mouse thymoma kinase (AKT) axis, relevant to M2 macrophage activation (Figure ). The latter appears to proceed via a PI3K‐ mTORC2 axis that activates the transcription factor IRF4 .…”
Section: Il‐4rα Signalling and Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to STAT6 activation, the IL‐4R complexes activate other signalling pathways that contribute to the regulation of allergic responses. One pathway involves the binding of the insulin receptor substrate 1/2 (IRS1/2) proteins at Y500 of the human IL‐4Rα, which then act to link the IL‐4R with several downstream signalling pathways, most notably the phosphoinositide 3‐kinases (PI3K)‐AKR mouse thymoma kinase (AKT) axis, relevant to M2 macrophage activation (Figure ). The latter appears to proceed via a PI3K‐ mTORC2 axis that activates the transcription factor IRF4 .…”
Section: Il‐4rα Signalling and Mechanism Of Actionmentioning
confidence: 99%
“…The latter appears to proceed via a PI3K‐ mTORC2 axis that activates the transcription factor IRF4 . In turn, IRS2‐dependent signalling is negatively regulated by suppressor of cytokine signalling 1 (Socs1)‐dependent ubiquitination (Figure ). Notwithstanding these results, a negative regulatory function of the IRS‐2 pathway in regulating the allergic response has been demonstrated using in vivo genetic approaches.…”
Section: Il‐4rα Signalling and Mechanism Of Actionmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assay. ChIP assay was performed as previously described with slight modification (17). β-catenin antibody was used, and qPCR was performed with specific primers to the slug promoter.…”
Section: Signaling Experimentsmentioning
confidence: 99%
“…They suggest that regulation of SOCS1 mainly affects hematopoietic cells, not epithelial cells. McCormick et al showed that reduced expression of SOCS1 has been shown to prolong IL-4-induced IRS-2 tyrosine phosphorylation and enhanced M2 differentiation (72). IRS-2 also plays a major role in allergic lung inflammation and remodeling (73).…”
Section: Discussionmentioning
confidence: 99%